Peat decomposition – shaping factors, significance in environmental studies and methods of determination; a literature review - Drzymulska, Danuta (Instytut Geologii UAM, 2016)
A review of literature data on the degree of peat decomposition – an important parameter that yields data on environmental conditions during the peat-forming process, i.e., humidity of the mire surface, is presented. A decrease in the rate of peat decomposition indicates a rise of the ground water table. In the case of bogs, which receive exclusively atmospheric (meteoric) water, data on changes in the wetness of past mire surfaces could even be treated as data on past climates. Different factors shaping the process of peat decomposition are also discussed, such as humidity of the substratum and climatic conditions, as well as the chemical composition of peat-forming plants. Methods for the determination of the degree of peat decomposition are also outlined, maintaining the division into field and laboratory analyses. Among the latter are methods based on physical and chemical features of peat and microscopic methods. Comparisons of results obtained by different methods can occasionally be difficult, which may be ascribed to different experience of researchers or the chemically undefined nature of many analyses of humification.
Keywords: plant remains; humification; microscopic view of peat; humidity of mire surface; palaeoclimate